Glavne značilnosti poporodne depresije - Mivšek, Ana Polona (Obzornik zdravstvene nege, 2005)
Post-partum depression affects 10 to 15% of women. It usually occurs in the fcrst post-partum year, most often in the first post-partum month but in some cases already during pregnancy. Etiology is not clearly defined and survey of literature on risk factors inconsistent. Symptoms could be easily mistaken forthe symptoms of puerperium as it usually occurs in the period when the relation.s between mother and child are not yet established and can therefore have adverse effects of child's development and progress. Therefore, it requires full attention of all health workers.
Keywords: depresija; Depresija poporodna; Depression, Postpartum; Diagnosis; etiologija; Etiology; poporodna depresija